REGIONALIZATION OF PHYSICAL THERAPY SERVICES: : CHALLENGES AND BARRIERS TO ACCESS TO TREATMENT (PRÁXIS EM SAÚDE, 2026)
Health is a fundamental human right, and it is the duty of the State to provide the indispensable conditions for its full exercise, in which Physical Therapy plays an essential role within primary health care. This study aimed to identify barriers to access to Physical Therapy after hospital discharge through the application of a structured questionnaire focused on patients’ conditions of access to treatment, and it was approved by the Research Ethics Committee (CEP No. 6,678,630). A total of 175 patients participated, of whom 90.86% had an income equal to or less than one minimum wage; 84% reported that they would not be able to afford such treatment, and 63.43% did not even receive guidance regarding post-discharge Physical Therapy. The study shows that factors such as the lack of guidance when referring patients to physical therapists after discharge, as well as the social vulnerability experienced by patients, create barriers to access to Physical Therapy services after hospital discharge.
Keywords: Public Health; Physical Therapy; Trauma and Orthopedics